Kewenangan Notaris Dalam Menerapkan Prinsip Mengenali Pengguna Jasanya Pada Permenkumham Nomor 9 Tahun 2017 - Gede Odhy Suryawiguna Robed; I Gede Yusa (Fakultas Hukum, Universitas Warmadewa, 2024)
The aim of this study is to examine the extent of authority that can be exercised by a notary in reporting suspicious financial transactions and what the notary's responsibilities are in implementing the principle of recognizing users of his services in accordance with the provisions of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 9 of 2017 concerning the Application of Principles. Recognizing Service Users for Notaries. This study uses normative legal research methods with a legislative approach and analysis of legal concepts. The results of the study show that if you look at the principle of lex superior derogate legi inferior then in the legal hierarchy Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary Public has a higher position than the Regulation of the Minister of Law and Human Rights Number 9 of 2017 concerning the Implementation of the Principle of Recognizing Service Users for Notaries, therefore notaries must maintain the confidentiality of the deeds they make based on the provisions of Article 16 paragraph (1) letter f and the notary's responsibility is only based on formal truth in accordance with the provisions of Article 39 Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary.